2010
DOI: 10.1515/znc-2010-9-1007
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Stimulant in Cinnamomum camphora for the Common Bluebottle, Graphium sarpedon nipponum (Lepidoptera: Papilionidae)

Abstract: The acceptance of camphor tree (Cinnamomum camphora) as a host plant for the larvae of common bluebottle (Graphium sarpedon nipponum) was explained by the presence of feeding stimulants in the leaves. When the active methanol extract of C. camphora leaves was separated into hexane and water layers, both layers showed high feeding activities for the larvae of G. sarpedon nipponum. Bioassay-guided fractionation of the hexane layer resulted in the isolation of a highly active compound, which was identifi ed as α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Plant odors, which are complex blends of dozens, if not hundreds of chemicals, are thought to have specific compounds, unique for different plants that are attractive to insects (e.g., [13]). It has been shown that electroantennographic responses can be elicited from butterflies with volatiles collected from the leaves of their corresponding host plants (e.g., [19][20][21]). Butterflies can be stimulated to lay eggs on certain plants by specific volatile compounds, as well as deterred from doing so by others (e.g., [22][23][24][25][26][27]).…”
Section: Introductionmentioning
confidence: 99%
“…Plant odors, which are complex blends of dozens, if not hundreds of chemicals, are thought to have specific compounds, unique for different plants that are attractive to insects (e.g., [13]). It has been shown that electroantennographic responses can be elicited from butterflies with volatiles collected from the leaves of their corresponding host plants (e.g., [19][20][21]). Butterflies can be stimulated to lay eggs on certain plants by specific volatile compounds, as well as deterred from doing so by others (e.g., [22][23][24][25][26][27]).…”
Section: Introductionmentioning
confidence: 99%